Answer:
36 : 6 and -6
12 = ![2\sqrt{3} , -2\sqrt{3}](https://tex.z-dn.net/?f=2%5Csqrt%7B3%7D%20%2C%20%20-2%5Csqrt%7B3%7D)
1.96 =1.4 and -1.4
0.64 : 0.8 and -0.8
400 : 20 and -20
25/36 = 5/6 and -5/6
Step-by-step explanation:
we know that
(-x)^2 = x^2
ALSO
(x)^2 = x^2
thus, square of both negative and positive number is same positive number.
_________________________________________________
36 = 6*6
36 = -6*-6
hence
square roots of 36 is both -6 and 6
12 = 4*3 =
![\sqrt{12} = 2\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B12%7D%20%3D%202%5Csqrt%7B3%7D)
also
12 = ![-2\sqrt{3} *-2\sqrt{3}](https://tex.z-dn.net/?f=-2%5Csqrt%7B3%7D%20%2A-2%5Csqrt%7B3%7D)
![\sqrt{12} = -2\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B12%7D%20%3D%20-2%5Csqrt%7B3%7D)
___________________________________
1.96 = 196/100 = (14/10)^2
1.96 = 196/100 = (-14/10)^2
hence
![\sqrt{1.96} = 14/10 \ or -14/10](https://tex.z-dn.net/?f=%5Csqrt%7B1.96%7D%20%20%3D%2014%2F10%20%20%5C%20or%20-14%2F10)
_______________________________
0.64 = 64/100 = (8/10)^2 = 0.8^2
0.64 = 64/100 = (-8/10)^2 = (-0.8)^2
Thus, square root of 0.64 = 0.8 and -0.8
_________________________________
400 = 20^2
400 = (-20)^2
![\sqrt{400} = 20\\\sqrt{400} = -20\\](https://tex.z-dn.net/?f=%5Csqrt%7B400%7D%20%20%3D%2020%5C%5C%5Csqrt%7B400%7D%20%20%3D%20-20%5C%5C)
__________________________________
25/36 = (5/6)^2
25/36 = (-5/6)^2
![\sqrt{ 25/36} = 5/6 \\\sqrt{ 25/36} = (-5/6](https://tex.z-dn.net/?f=%5Csqrt%7B%2025%2F36%7D%20%3D%205%2F6%20%5C%5C%5Csqrt%7B%2025%2F36%7D%20%3D%20%28-5%2F6)